Fahmy's four quadrant sutures: a new technique for control of blood loss during cesarean delivery for placenta previa - Fahmy, Mohamed S.; Ezzat, Laila; Khalil, Maraey M.; Elsayed, Ahmed H.; Fahmy, Sherif S.; Badawy, Adham; Ramadan, Hossam; Abbas, Ahmed M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of this study is to assess the efficacy and safety of Fahmy's four quadrant suture technique (FFQS) in controlling blood loss during cesarean delivery for placenta previa (PP). Methods: The study was carried out in a tertiary University Hospital between January 2017 to December 2017 involved 12 women with heavy bleeding occurred after removal of the placenta from the lower section during cesarean delivery for PP. The FFQS technique consisted of two sutures to ligate the uterine branches on both sides and two sutures on the anterior and posterior wall of the lower uterine segment. Details regarding the management and maternal outcomes were recorded. Results: The mean age of the study participants was 29.58±5.29 years and the mean parity was 2.25±1.14. The mean gestational age at termination of pregnancy was 36.91±1.38 weeks. The mean duration of the whole surgery was 78.75±43.28 minutes, while the mean duration of FFQS technique was only 10±2.09 minutes. The technique was exclusively effective in 8 out of 12 cases (66.67%) while 2 cases needed bilateral internal iliac artery ligation and 2 cases needed hysterectomy. The mean amount of blood loss in all cases was 2433.33±833.76 ml. the mean amount of transfused packed RBCs was 3.92±1.68 units and fresh frozen plasma (FFP) was 3.42±1.44 units. All cases had uneventful postoperative course and no mortality cases in present series. Conclusions: The new technique; FFQS represents a rapid, effective, and inexpensive opportunity for women with bleeding from the lower segment of uterus due to PP. This simple procedure should be attempted before other complex measures to achieve good hemostasis.